The promises and perils of circulating tumor DNA for monitoring immunotherapy response in non-small cell lung cancer - Brandon Joseph Hebert; James Bradley (Exploration of Targeted Anti-tumor Therapy)
There has been a rapid expansion of immunotherapy options for non-small cell lung cancer (NSCLC) over the past two decades, particularly with the advent of immune checkpoint inhibitors. Despite the emerging role of immunotherapy in adjuvant and neoadjuvant settings though, relatively few patients will respond to immunotherapy which can be problematic due to expense and toxicity; thus, the development of biomarkers capable of predicting immunotherapeutic response is imperative. Due to the promise of a noninvasive, personalized approach capable of providing comprehensive, real-time monitoring of tumor heterogeneity and evolution, there has been wide interest in the concept of using circulating tumor DNA (ctDNA) to predict treatment response. Although the use of ctDNA to detect actionable mutations such as EGFR is now integral in the standard of care for patients with NSCLC, several large studies have also shown its potential as a biomarker of immunotherapeutic response. Ongoing ctDNA interventional clinical trials, such as the BR.36 trial, will help to clarify the potential role of ctDNA for therapeutic guidance. Despite the promise of this technology, there are many limitations and considerations that clinicians need to be aware of prior to widespread implementation in clinical practice, such as the effect of underlying comorbidities, ctDNA fraction, stage of underlying malignancy, and concordance between aberrations detected in ctDNA and tumor tissue.